Small business management : an applied approach - Mazzarol, Tim , 1957-; Reboud, Sophie (Prahran, Victoria : Tilde University Press, 2011)
The aim of this text is to familiarise students with the theory and practice of small business management and challenge assumptions that may be held about the way small business management can or should adopt the management practices of larger firms
1. The role of the small business within the economy and government policy -- 2. Entrepreneurs versus owner-managers : theories of new venture creation -- 3. Surviving the early years : screening the business opportunity -- 4. The process of planning and strategy in the small firm -- 5. Creating customers -- 6. Financing the small firm part 1 : debt versus equity -- 7. Financing the small firm part 2 : cash flows, profit and working capital -- 8. The process of growth in the small firm -- 9. Small firms and human resources : coaching and building teams -- 10. Franchising and legal issues for small business -- 11. Small firms and family business -- 12. The owner-manager and the troubled company -- 13. Buying, selling and valuing the business
Includes bibliographical references and index
Keywords: Small business -- Management